Influence of combined probiotics Lactobacillus sporogenes and Bacillus subtilis on survival, growth, biochemical changes and energy utilization performance of Macrobrachium rosenbergii (De Man 1879) post larvae - Seenivasan, C; Radhakrishnan, S; Muralisankar, T; Saravana Bhavan, P (Journal of Ecobiotechnology, 2012)
A 90-day feeding experiment was studied to determine the influence of the bacterial combination Lactobacillus sporogenes and Bacillus subtilis (LS+BS) on survival, growth, biochemical constituents and energy utilization performance of the freshwater prawn Macrobrachium rosenbergii post larvae (PL). Experimental diets were the same, except for the variation in probiotic levels. The probiotics LS+BS (4:3) were used at 0%, 1%, 2%, 3% and 4% inclusion rates in the experimental diets. After the feeding trail, the growth parameters of the PLs, such as survival, weight gain, specific growth rate, feed conversion efficiency and protein efficiency rate were significantly (P<0.05) higher in 4% LS+BS incorporated diet as compared with control. The food conversion ratio was significantly (P<0.05) lower in 4% LS+BS incorporated diet. The biochemical composition of the total protein, amino acid, carbohydrate and lipid ash content were significantly (P<0.05) higher in 4% LS+BS incorporated diet. However, insignificant difference was recorded in moisture content between control and experimental groups. The energy utilization parameters, such as feeding rate, absorption rate, conversion rate and metabolic rate were significantly (P<0.05) higher in 4% LS+BS incorporated diet fed PL. These results revealed the benefits of the incorporation of the probiotic (LS+BS) in aqua feed for M. rosenbergii PL.